Separation and recovery of organic acids from fermented kitchen waste by an integrated process - Omar, Farah Nadia; Abdul Rahman, Nor'aini; Hafid, Halimatun Saadiah; Phang, Lai Yee; Hassan, Mohd Ali (Academic Journals, 2009)
Organic acids produced from anaerobic digestion of kitchen waste were recovered using a new integrated method which consisted of freezing and thawing, centrifugation, filtration and evaporation. The main organic acid produced was lactic acid (98%). After the freezing and thawing process, 73% of the total suspended solids were removed and the organic acids were elevated from 59.0 to 70 g/L. The evaporation technique was used to further concentrate the organic acids up to 224 g/L. Using the integrated recovery method, the reduction of the total suspended solids in the solution achieved was about 93%. The material balance for the recovery process was also presented.